Ginkgo Biloba and Long COVID: In Vivo and In Vitro Models for the Evaluation of Nanotherapeutic Efficacy - Thelma Akanchise; Angelina Angelova (MDPI AG, 2023)
Coronavirus infections are neuroinvasive and can provoke injury to the central nervous system (CNS) and long-term illness consequences. They may be associated with inflammatory processes due to cellular oxidative stress and an imbalanced antioxidant system. The ability of phytochemicals with antioxidant and anti-inflammatory activities, such as Ginkgo biloba, to alleviate neurological complications and brain tissue damage has attracted strong ongoing interest in the neurotherapeutic management of long COVID. Ginkgo biloba leaf extract (EGb) contains several bioactive ingredients, e.g., bilobalide, quercetin, ginkgolides A-C, kaempferol, isorhamnetin, and luteolin. They have various pharmacological and medicinal effects, including memory and cognitive improvement. Ginkgo biloba, through its anti-apoptotic, antioxidant, and anti-inflammatory activities, impacts cognitive function and other illness conditions like those in long COVID. While preclinical research on the antioxidant therapies for neuroprotection has shown promising results, clinical translation remains slow due to several challenges (e.g., low drug bioavailability, limited half-life, instability, restricted delivery to target tissues, and poor antioxidant capacity). This review emphasizes the advantages of nanotherapies using nanoparticle drug delivery approaches to overcome these challenges. Various experimental techniques shed light on the molecular mechanisms underlying the oxidative stress response in the nervous system and help comprehend the pathophysiology of the neurological sequelae of SARS-CoV-2 infection. To develop novel therapeutic agents and drug delivery systems, several methods for mimicking oxidative stress conditions have been used (e.g., lipid peroxidation products, mitochondrial respiratory chain inhibitors, and models of ischemic brain damage). We hypothesize the beneficial effects of EGb in the neurotherapeutic management of long-term COVID-19 symptoms, evaluated using either in vitro cellular or in vivo animal models of oxidative stress.